Analisis Blackbox Testing dan User Acceptance Testing terhadap Sistem Informasi Posyandu Dondang - Fahrullah, Fahrullah; Haerullah, Haerullah; Ridhawani, Achmad (DPPM Universitas Pelita Bangsa, 2025)
Posyandu (Integrated Service Post) is one form of Community-Based Health Effort that plays an important role in basic community health services. Information processing activities at Posyandu Dondang are still done manually (written by hand), so it is necessary to develop a website-based Posyandu information system to make it easier for Posyandu cadres to manage data, make reports, and provide information to the community more effectively and efficiently. This study aims to test the website-based Posyandu Dondang information system using the User Acceptance Testing (UAT) method. This system was developed to facilitate data management and services at Posyandu with four main user groups: admins, parents, midwives, and officers. Testing was carried out using the UAT method involving 21 respondents and using a Likert scale to measure the level of user acceptance. Based on the results of the analysis, the results of the system functionality test showed that most of the features were running well, although there were still some features that needed improvement such as the profile menu, settings, and activities, while the User Acceptance Testing (UAT) / user acceptance rate was 92.06%, which indicates that the system is in the